Imagination and Its Aesthetic and Pedagogical Dimensions in Educational Theatre Performances - rida, Rida Abdul-Abu Al-Dhar Abd; Ibrahim, Duaa Basem (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
Considering the continuous development of teaching methods, it has become necessary to search for innovative means that combine the pedagogical and aesthetic aspects in order to create a stimulating and influential educational environment. Educational theatre is considered one of the effective tools that combine art and education. The current research (The Role of Imagination in Enhancing the Aesthetic and Pedagogical Dimensions in Educational Theatre) included in the first chapter the research problem, which the researcher inquired about in the question: What is the role of imagination in enhancing the aesthetic and pedagogical dimensions in educational theatre? The importance of the research and the need for it lie in providing a practical vision for directors and those interested in theatre on how to employ imagination, and it contributes to enriching artistic and pedagogical literature with analytical and correlative material between imagination, education, and aesthetics. The boundaries of the research were represented by Spatial boundary: Performances presented in the School Activity Hall in Wasit Governorate. Temporal boundary: 2017–2018. Subject boundary: Knowing the role of imagination in enhancing the aesthetic and pedagogical dimensions in educational theatre. The chapter concluded with the definition of terms and the operational definition. The second chapter included three sections: the first entitled Imagination, the second Aesthetics and Aesthetic Dimensions, and the third Education and Pedagogical Dimensions. The chapter concluded with what the theoretical framework revealed. The third chapter included the research community and its purposively selected sample, which consisted of one performance (When the Blood Spoke, 2017). The researcher adopted the indicators of the theoretical framework as a tool for his research and adopted the descriptive method because it is close to the research mechanism. The research concluded with results, the most important of which is that imagination contributes to forming a theatrical vision that stimulates learning. The study showed that integrating imagination into educational theatre creates an open educational space that helps in understanding concepts in a non-traditional way, based on intellectual stimulation and emotional immersion.